The Relationship Between Multiple Immunization Injections and Post-Immunization Adverse Events in Infants - Cholila, Nur; Wulansari, Citra Dewi (INTERNATIONAL JOURNAL OF MIDWIFERY RESEARCH, 2024)
Introduction: COVID-19 has resulted in a decrease in the coverage of complete routine immunization of children . To increase the coverage of immunization, the government issued a circular regarding the provision of multiple immunization injections. The provision of multiple immunization injections resulted in post-immunization adverse events This study aims to determine whether there is a relationship between the provision of multiple injections and post-immunization adverse events Method: This research is an analytical survey using a cross-sectional approach , with a population of 80 respondents selected by simple random sampling, 60 respondents were obtained. The independent variable is infants who received multiple immunization injections and the dependent variable is post-immunization follow-up events using the contingency coefficient test.Result: The results of the study conducted on infants who underwent immunization at UOBF Puskesmas Tuban after being analyzed using SPSS showed a contingency coefficient test. p-value 0.009 (p <0.05) which means reject . Therefore, it can be concluded that with a 95% confidence level, there is a Relationship between Multiple Immunization Injections and Post-Immunization Adverse Events in Infants at UOBF Tuban Health Center .Conclusion: The description above concludes that there is a relationship between the administration of multiple immunization injections and post-immunization adverse events at a mild level and no one experienced post-immunization adverse events at a severe level.